Preparation method and application of functional diaphragm of aqueous zinc ion battery
By constructing a functional separator on the glass fiber membrane, the polymer molecular chain and zinc-containing compound-containing complex guide the uniform deposition of zinc ions, the problem of zinc negative electrode dendrites piercing the separator is solved, and the circulation performance and life of aqueous zinc ion batteries are significantly improved.
Patent Information
- Application Number
- CN202411887602.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-20
AI Technical Summary
The growth of zinc negative electrode dendrites in aqueous zinc ion batteries pierce the separator, causing a short circuit in the battery, and the hydrogen evolution reaction and zinc negative corrosion affect the battery life.
The polymer molecular chain and zinc-containing compound complex were used to grow in situ on the glass fiber membrane to construct a functional membrane to guide the uniform deposition of zinc ions and inhibit dendrites' growth.
Effectively inhibit the puncture of zinc negative electrode dendrites of the diaphragm, improve battery circulation performance, and significantly extend the battery service life.
Smart Images

Figure CN119725981A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of battery materials, and in particular to a preparation method and application of a functionalized diaphragm for an aqueous zinc ion battery. Background Art
[0002] As the demand for energy rises rapidly, aqueous zinc-ion batteries stand out among many energy storage batteries. Aqueous zinc-ion batteries have extremely high ionic conductivity, and aqueous electrolytes are safer and more environmentally friendly than the mainstream organic electrolytes of lithium batteries. In addition, high-capacity zinc metal anodes can partially compensate for the energy density loss caused by voltage limitations, and zinc metal reserves are abundant and inexpensive. Therefore, aqueous zinc-ion batteries are of great significance in the future development of energy storage.
[0003] In actual use, aqueous zinc ions still face many key problems. First, mainly due to the unlimited two-dimensional diffusion behavior of zinc ions and the uneven electric field distribution, the zinc negative electrode dendrites grow and pierce the diaphragm, causing the battery to short-circuit. The dendrites detached from the negative electrode will also reduce the Coulomb effect. Secondly, the hydrogen evolution reaction (HER) caused by aqueous electrolytes and the corrosion passivation of the zinc negative electrode are important issues that affect the life of zinc batteries.
[0004] As one of the important components of the battery, the separator blocks the direct contact between the positive and negative electrodes and regulates the migration of zinc ions. Glass fiber is a commonly used battery separator, but the glass fiber membrane has poor mechanical properties, low ionic conductivity, and its zinc affinity induces Zn 2+ Growth towards the separator can easily pierce the separator, causing a short circuit in the battery. Functional modification of the separator is a feasible solution to improve its performance. Summary of the invention
[0005] The present invention aims to solve the problem that zinc negative electrode dendrites grow and pierce the diaphragm, causing battery short circuit, and provides a preparation method and application of a functionalized diaphragm for an aqueous zinc ion battery. The present invention prepares a diaphragm material with uniform pore size and negative charge, and introduces negatively charged long-chain molecules to allow zinc ions to be transported along the long chains, guiding the uniform deposition of zinc ions during the battery cycle, thereby effectively inhibiting the growth of zinc negative electrode dendrites from piercing the diaphragm, and finally obtaining an aqueous zinc ion battery with excellent cycle performance.
[0006] The technical solutions adopted are:
[0007] A method for preparing a functionalized diaphragm for an aqueous zinc ion battery comprises the following steps:
[0008] (1) Adding polymer molecular chains to aqueous solution and mixing them thoroughly with ultrasound;
[0009] (2) dispersing the zinc-containing compound in the solution and mixing it evenly by ultrasonic mixing;
[0010] (3) mixing the solutions prepared in step (1) and step (2), and mixing them uniformly by ultrasonic mixing;
[0011] (4) completely wetting the glass fiber separator in the mixed solution of step (3), and suspending the glass fiber separator in the mixed solution and allowing it to stand;
[0012] (5) Rinse the prepared diaphragm and dry it.
[0013] Preferably, in step (1), the polymer molecule is sodium poly(p-styrene sulfonate).
[0014] Preferably, the mass concentration of the poly(sodium p-styrene sulfonate) used is 0-4%.
[0015] Preferably, in step (2), the zinc-containing compound is zinc chloride, zinc sulfate, zinc acetylacetonate, zinc trifluoromethanesulfonate, or zinc bis(trifluoromethylsulfonyl)imide.
[0016] Preferably, the concentration of the zinc-containing compound after mixing with the solution is 0 to 5%.
[0017] Preferably, in step (2), the solution is a mixture of one or more of water, dichloromethane, n-hexane and hexadecane.
[0018] Preferably, in step (4), the glass fiber separator is completely wetted at room temperature and allowed to stand at room temperature for 12 to 48 hours.
[0019] Preferably, in step (5), the prepared membrane is rinsed with deionized water for 2 to 5 times.
[0020] Preferably, after rinsing, the product is dried in a drying oven at 60° C. for 12 hours.
[0021] The diaphragm prepared by the preparation method of the present invention is used in an aqueous zinc ion battery. The functionalized diaphragm of the aqueous zinc ion battery guides the uniform deposition of zinc ions during the battery cycle, thereby effectively inhibiting the growth of zinc negative electrode dendrites from piercing the diaphragm, and finally obtaining an aqueous zinc ion battery with excellent cycle performance.
[0022] The principle of the present invention is to use a complex of poly(sodium p-styrene sulfonate) and a zinc-containing compound to grow in situ on the glass fiber surface of the glass fiber membrane to construct a functional diaphragm. Under an external electric field, because a large number of negatively charged sulfonic acid groups are evenly attached to the surface of the diaphragm, the zinc ions are first guided to be evenly dispersed on the surface of the diaphragm. At the same time, there are also negatively charged sulfonic acid groups in the pores of the diaphragm. Because there is an electrostatic attraction between the sulfonic acid groups and the zinc ions, the zinc ions can move quickly in the pores of the diaphragm, thereby successfully constructing a zinc ion fast migration channel, allowing Zn 2+The pore size distribution of the diaphragm surface after in-situ growth is more uniform and the size is further reduced, which is also beneficial to Zn 2+ uniform deposition.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] The present invention prepares a mixed solution of a polymer molecular chain and a complex containing a zinc compound, and suspends a glass fiber membrane in the mixed solution and allows the membrane to be modified. The membrane is then dried to obtain a modified functionalized membrane. The preparation process is very simple, and the cycle stability can be increased to more than 14 times the original under the same test conditions, showing a broad application prospect. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 Surface electron microscope (SEM) image of the glass fiber membrane of the comparative example of the present invention;
[0026] Figure 2 This is a surface electron microscope (SEM) image of the functionalized glass fiber membrane of Example 7 of the present invention;
[0027] Figure 3 Surface X-ray photoelectron spectroscopy (XPS) diagram of the glass fiber membrane of the comparative example of the present invention and the functionalized glass fiber membrane prepared in Example 7;
[0028] Figure 4 This is a high-resolution XPS peak diagram of the zinc element of the glass fiber membrane of the comparative example of the present invention;
[0029] Figure 5 This is a high-resolution XPS peak diagram of the zinc element of the functionalized glass fiber membrane of Example 7 of the present invention. DETAILED DESCRIPTION
[0030] The accompanying drawings are only used for illustrative purposes; the present invention will be further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the technical solution of the present invention is not limited to the following embodiments.
[0031] In the following examples, the cycle stability test was carried out at 25°C.
[0032] Comparison example
[0033] This comparative example provides a method for treating a glass fiber diaphragm, comprising the following steps:
[0034] (1) Add deionized water into the beaker and perform ultrasonic treatment
[0035] (2) The glass fiber separator is completely wetted in the aqueous solution at room temperature, suspended in the aqueous solution, and allowed to stand at room temperature for 24 hours.
[0036] (3) Rinse the diaphragm three times with deionized water
[0037] (4) The obtained membrane was dried at 60°C for 12 h.
[0038] The glass fiber separator treated by the above method was used to assemble a button battery and the battery cycle stability test was carried out. -2 The current density is 0.1 mAh cm -2 The cycle can be maintained for up to 130 hours at an area capacity of 1.
[0039] Example 1
[0040] A method for preparing a functionalized diaphragm for an aqueous zinc ion battery comprises the following steps:
[0041] (1) Add sodium poly(p-styrene sulfonate) with a mass concentration of 4% into the aqueous solution and mix thoroughly by ultrasonication.
[0042] (2) Dissolve zinc chloride with a mass concentration of 0% in an aqueous solution and mix uniformly by ultrasonication.
[0043] (3) Mix the solutions prepared in step (1) and step (2), and mix them uniformly by ultrasonic mixing.
[0044] (4) At room temperature, the glass fiber separator is completely wetted in the mixed solution, suspended in the solution, and allowed to stand at room temperature for 12 hours.
[0045] (5) The membrane was rinsed with deionized water three times and dried at 60° C. for 12 h.
[0046] The glass fiber separator treated by the above method was used to assemble a button battery and the battery cycle stability test was carried out. -2 The current density is 0.1 mAh cm -2 The cycle can be maintained for up to 190 hours at an area capacity of 1.
[0047] Example 2
[0048] A method for preparing a functionalized diaphragm for an aqueous zinc ion battery comprises the following steps:
[0049] (1) Add sodium poly(p-styrene sulfonate) with a mass concentration of 4% into the aqueous solution and mix thoroughly by ultrasonication.
[0050] (2) Dissolve zinc chloride with a mass concentration of 2.5% in an aqueous solution and mix uniformly by ultrasonication.
[0051] (3) Mix the solutions prepared in step (1) and step (2), and mix them uniformly by ultrasonic mixing.
[0052] (4) At room temperature, the glass fiber separator is completely wetted in the mixed solution, suspended in the solution, and allowed to stand at room temperature for 12 hours.
[0053] (5) The membrane was rinsed with deionized water three times and dried at 60° C. for 12 h.
[0054] The glass fiber separator treated by the above method was used to assemble a button battery and the battery cycle stability test was carried out. -2 The current density is 0.1 mAh cm -2 The cycle can be maintained for up to 500h at an area capacity of 1.54kWh.
[0055] Example 3
[0056] A method for preparing a functionalized diaphragm for an aqueous zinc ion battery comprises the following steps:
[0057] (1) Add sodium poly(p-styrene sulfonate) with a mass concentration of 4% into the aqueous solution and mix thoroughly by ultrasonication.
[0058] (2) Dissolve zinc chloride with a mass concentration of 5% in an aqueous solution and mix uniformly by ultrasonication.
[0059] (3) Mix the solutions prepared in step (1) and step (2), and mix them uniformly by ultrasonic mixing.
[0060] (4) At room temperature, the glass fiber separator is completely wetted in the mixed solution, suspended in the solution, and allowed to stand at room temperature for 12 hours.
[0061] (5) The membrane was rinsed with deionized water three times and dried at 60° C. for 12 h.
[0062] The glass fiber separator treated by the above method was used to assemble a button battery and the battery cycle stability test was carried out. -2 The current density is 0.1 mAh cm -2 The cycle can last up to 450h at the area capacity.
[0063] Example 4
[0064] A method for preparing a functionalized diaphragm for an aqueous zinc ion battery comprises the following steps:
[0065] (1) Add sodium poly(p-styrene sulfonate) with a mass concentration of 0% into the aqueous solution and mix thoroughly by ultrasonication.
[0066] (2) Dissolve zinc chloride with a mass concentration of 2.5% in an aqueous solution and mix uniformly by ultrasonication.
[0067] (3) Mix the solutions prepared in step (1) and step (2), and mix them uniformly by ultrasonic mixing.
[0068] (4) At room temperature, the glass fiber separator is completely wetted in the mixed solution, suspended in the solution, and allowed to stand at room temperature for 12 hours.
[0069] (5) The membrane was rinsed with deionized water three times and dried at 60° C. for 12 h.
[0070] The glass fiber separator treated by the above method was used to assemble a button battery and the battery cycle stability test was carried out. -2 The current density is 0.1 mAh cm -2 The cycle can be maintained for up to 200 hours at an area capacity of 1.
[0071] Example 5
[0072] A method for preparing a functionalized diaphragm for an aqueous zinc ion battery comprises the following steps:
[0073] (1) Add 2% sodium poly(p-styrene sulfonate) into the aqueous solution and mix thoroughly by ultrasonication.
[0074] (2) Dissolve zinc chloride with a mass concentration of 2.5% in an aqueous solution and mix uniformly by ultrasonication.
[0075] (3) Mix the solutions prepared in step (1) and step (2), and mix them uniformly by ultrasonic mixing.
[0076] (4) At room temperature, the glass fiber separator is completely wetted in the mixed solution, suspended in the solution, and allowed to stand at room temperature for 12 hours.
[0077] (5) The membrane was rinsed with deionized water three times and dried at 60° C. for 12 h.
[0078] The glass fiber separator treated by the above method was used to assemble a button battery and the battery cycle stability test was carried out. -2 The current density is 0.1 mAh cm -2 The cycle can be maintained for up to 1000h at an area capacity of 1.
[0079] Example 6
[0080] A method for preparing a functionalized diaphragm for an aqueous zinc ion battery comprises the following steps:
[0081] (1) Add 2% sodium poly(p-styrene sulfonate) into the aqueous solution and mix thoroughly by ultrasonication.
[0082] (2) Dissolve zinc chloride with a mass concentration of 2.5% in an aqueous solution and mix uniformly by ultrasonication.
[0083] (3) Mix the solutions prepared in step (1) and step (2), and mix them uniformly by ultrasonic mixing.
[0084] (4) At room temperature, the glass fiber separator is completely wetted in the mixed solution, suspended in the solution, and allowed to stand at room temperature for 48 hours.
[0085] (5) The membrane was rinsed with deionized water three times and dried at 60° C. for 12 h.
[0086] The glass fiber separator treated by the above method was used to assemble a button battery and the battery cycle stability test was carried out. -2 The current density is 0.1 mAh cm -2 The cycle can be maintained for up to 1200h at an area capacity of 1.
[0087] Example 7
[0088] A method for preparing a functionalized diaphragm for an aqueous zinc ion battery comprises the following steps:
[0089] (1) Add 2% sodium poly(p-styrene sulfonate) into the aqueous solution and mix thoroughly by ultrasonication.
[0090] (2) Dissolve zinc chloride with a mass concentration of 2.5% in an aqueous solution and mix uniformly by ultrasonication.
[0091] (3) Mix the solutions prepared in step (1) and step (2), and mix them uniformly by ultrasonic mixing.
[0092] (4) At room temperature, the glass fiber separator is completely wetted in the mixed solution, suspended in the solution, and allowed to stand at room temperature for 24 hours.
[0093] (5) The membrane was rinsed with deionized water three times and dried at 60° C. for 12 h.
[0094] The glass fiber separator treated by the above method was used to assemble a button battery and the battery cycle stability test was carried out. -2 The current density is 0.1 mAh cm -2 The cycle can be maintained for up to 1800h at the area capacity.
[0095] The functionalized modified membrane prepared by the above method was subjected to a 0.1 mA cm -2The current density is 0.1 mAh cm -2 The cycle stability test was carried out under the area capacity of , and the test results of the battery separators prepared under different conditions are shown in Table 1.
[0096] Table 1 Battery cycle stability performance (0.1 mA cm) of Examples 1-7 and Control Examples -2 0.1mAh cm -2 )Test Results
[0097]
[0098]
[0099] From the test results of Examples 1-7 and the control example in Table 1, when the mass concentration of poly(p-styrene sulfonate) sodium remains unchanged, the cyclic stability increases first and then decreases with the increase of zinc chloride concentration; when the mass concentration of zinc chloride remains unchanged, the cyclic stability increases first and then decreases with the increase of poly(p-styrene sulfonate) sodium concentration; the reason is that when the added concentration is too low, the complex is unevenly distributed; when the added concentration is too high, the complex blocks the pore size too much, affecting the Zn 2+ When the concentration of additives is kept constant, the cyclic stability increases first and then decreases with the increase of static time. The reason is that if the time is too short, the complex is unevenly distributed. If the time is too long, the complex will precipitate too much and block the pore size, affecting the Zn 2+ The maximum cycle stability duration is 1800h, which is 14 times that of the control example.
[0100] We performed electron microscopy on the functionalized modified membranes prepared in the control example and Example 7. Figure 1 and Figure 2 As shown, Figure 1 Electron microscopic images of the membrane surface of the diaphragm (GF) prepared as the control example at different magnifications. Figure 2 Electron microscopic images of the membrane surface of the aqueous zinc ion battery functionalized membrane (GF / PSS-ZnCl2) prepared in Example 7 at different magnifications, for comparison Figure 1 and Figure 2 It can be seen that the surface pore size of the functionalized modified diaphragm for aqueous zinc-ion batteries prepared by in-situ modification is smaller and more uniform.
[0101] Figure 3 Shown are X-ray photoelectron spectroscopy (XPS) graphs of the film surfaces of the control example and embodiment 7. Figure 4 , 5 The following are high-resolution XPS peak diagrams of zinc element on the surface of the control example diaphragm and the functionalized glass fiber membrane obtained in Example 7. Figure 4 and Figure 5It can be seen that in Example 7, the peak intensity of the zinc element is significantly increased after the glass fiber membrane is modified, proving that the complex is successfully grown in situ on the surface of the membrane.
[0102] Of course, the above description is not a limitation of the present invention, and the present invention is not limited to the above examples. Changes, modifications, additions or substitutions made by technicians in this technical field within the essential scope of the present invention should also fall within the protection scope of the present invention.
Claims
1. A method for preparing a functionalized diaphragm for an aqueous zinc ion battery, characterized in that: The steps include: (1) Adding polymer molecular chains to aqueous solution and mixing them thoroughly with ultrasound; (2) dispersing the zinc-containing compound in the solution and uniformly mixing by ultrasonic mixing; (3) mixing the solutions prepared in step (1) and step (2), and mixing them uniformly by ultrasonic mixing; (4) completely wetting the glass fiber separator in the mixed solution of step (3), and suspending the glass fiber separator in the mixed solution and allowing it to stand; (5) Rinse the prepared diaphragm and dry it.
2. The method for preparing a functionalized diaphragm for an aqueous zinc ion battery according to claim 1, wherein: In the step (1), the polymer molecule is sodium poly(p-styrene sulfonate).
3. The method for preparing a functionalized diaphragm for an aqueous zinc ion battery according to claim 2, wherein: The mass concentration of the used sodium poly(p-styrene sulfonate) is 0-4%.
4. The method for preparing a functionalized diaphragm for an aqueous zinc ion battery according to claim 1, wherein: In the step (2), the zinc-containing compound is zinc chloride, zinc sulfate, zinc acetylacetonate, zinc trifluoromethanesulfonate, or zinc bis(trifluoromethylsulfonyl)imide.
5. The method for preparing a functionalized diaphragm for an aqueous zinc ion battery according to claim 4, wherein: The concentration of the zinc-containing compound after mixing with the solution is 0 to 5%.
6. The method for preparing a functionalized diaphragm for an aqueous zinc ion battery according to claim 1, characterized in that: In the step (2), the solution is a mixture of one or more of water, dichloromethane, n-hexane and hexadecane.
7. The method for preparing a functionalized diaphragm for an aqueous zinc ion battery according to claim 1, characterized in that: In the step (4), the glass fiber separator is completely wetted at room temperature and allowed to stand at room temperature for 12 to 48 hours.
8. The method for preparing a functionalized diaphragm for an aqueous zinc ion battery according to claim 1, characterized in that: In the step (5), the prepared diaphragm is rinsed with deionized water for 2 to 5 times.
9. The method for preparing a functionalized diaphragm for an aqueous zinc ion battery according to claim 8, characterized in that: After rinsing, dry in a drying oven at 60°C for 12 hours.
10. Use of the diaphragm prepared as claimed in claims 1 to 9 in aqueous zinc ion batteries.
Citation Information
Patent Citations
Zinc ion battery negative electrode material based on boron nitride film and preparation method thereof
CN113851646A
Preparation method and application of zinc negative electrode with hydrophobic conductive polymer film
CN115692596A
Preparation method of modified PET-based aqueous zinc ion battery diaphragm
CN117039332A
Zinc ion battery based on ionic liquid-aqueous gel double-layer electrolyte and preparation method thereof
CN117594885A
Functional diaphragm for zinc ion battery as well as preparation method and application of functional diaphragm
CN118137067A